IDENTIFIKASI KESEHATAN TANAMAN BAKAU LAKI (Rhizophora mucronata Lamk) DI DESA BETUNG KECAMATAN KUSAN HILIR KABUPATEN TANAH BUMBU KALIMANTAN SELATAN - Rolin Okta Pamungkas; Normela Rachmawati; Susilawati Susilawati (Universitas Lambung Mangkurat, 2020)
Coastal areas of South Kalimantan show alarming conditions due to the reduction in mangrove plants. This situation will make the rate of environmental degradation relatively fast which will have an impact on displacement of settlements, ponds, gardens and damage to the shoulder of the road by coastal erosion. Facing this situation, planting was carried out in the former pond area with Mangrove species (Rhizophora) by the government of Tanah Bumbu Regency with PT. Arutmin in Betung Village in 2005. After planting, the condition of the mangrove stands also needs to be considered regarding health and damage. Therefore this effort was carried out with the aim of knowing the health and percentage of damage to Male Mangrove plants (Rhizophora mucronata Lamk). The results showed that of the 423 trees studied there were 390 trees with healthy criteria with a percentage of 93.38%. The highest percentage of damage based on the location of damage was found in leaves of 53.43%, canopy stem 44.50%, and roots of 2.07%. The highest percentage of damage was based on the cause of damage caused by pests 43.92% and plant competition 43.42%.Keywords: Beach; Male mangrove; Health; Damage